Evaluation Of The Role Of Novel Immunophenotypic Markers By Flow Cytometry In The Differential Diagnosis Of Acute Lymphoblastic Leukemia And Acute Myeloid Leukemia (The Review of Diabetic Studies, 2025)
Background: Accurate differentiation between acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) is essential for guiding therapy and predicting prognosis. While conventional morphological and immunophenotypic markers provide baseline diagnostic information, novel immunophenotypic markers may enhance the precision of lineage assignment, particularly in cases with ambiguous or overlapping features. Methods: A descriptive cross-sectional study was conducted on 100 newly diagnosed acute leukemia patients. Peripheral blood and bone marrow samples were analyzed using conventional cytochemistry and multiparametric flow cytometry. Both conventional markers (CD34, CD45, CD19, CD3, CD13, CD33, CD117) and novel markers (TdT, CD79a, CD123, CD7, CD56) were evaluated for expression patterns. Frequencies and percentages of marker expression were calculated, and comparative analysis between ALL and AML was performed.Results: Of the study population, 55% were diagnosed with ALL and 45% with AML. Conventional markers reliably distinguished most cases, with CD19 and CD3 predominantly expressed in ALL, and CD13, CD33, and CD117 in AML. Novel markers further improved diagnostic accuracy: TdT and CD79a were strongly associated with ALL (90.9% and 76.4%, respectively), while CD123 was more frequently expressed in AML (71.1%). Mixed or ambiguous lineage patterns were observed in 15% of cases, highlighting the added value of novel markers. Aberrant expression of CD7 and CD56 was detected in a minority of cases.Conclusion: The integration of conventional and novel immunophenotypic markers via flow cytometry significantly enhances the differential diagnosis of ALL and AML. Novel markers such as TdT, CD79a, and CD123 improve the accuracy of lineage assignment, particularly in ambiguous cases, supporting precise diagnosis, prognostication, and treatment planning.